Targeting RNA G‐quadruplexes as new treatment strategy for C9orf72 ALS/FTD - Martin H Schludi; Dieter Edbauer (EMBO Molecular Medicine)
Abstract The recent discovery of a pathogenic expansion of a (GGGGCC)n repeat in the C9orf72 gene in amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) led to a burst of mechanistic discoveries. In this issue, Simone et al (2018) describe novel compounds targeting the G‐quadruplex (G‐Q) structure of the (GGGGCC)n repeat RNA that alleviate the hallmarks of C9orf72 disease in patient‐derived neurons and increase survival in a Drosophila model. Lack of overt off‐target effects and toxicity suggest that these small molecules are promising lead compounds to the development of a therapy.